Polymorphism of the Rca2 anthracnose resistance gene in strawberry cultivars (Fragaria × ananassa) - A. S. Lyzhin; I. V. Lukyanchuk; E. V. Zhbanova (Труды по прикладной ботанике, генетике и селекции)
Background. Anthracnose, caused by phytopathogenic fungi of the genus Colletotrichum, is one of the most important strawberry diseases. Strawberry yield losses from anthracnose lesions can reach 80%. Most strawberry cultivars are susceptible to anthracnose. Therefore, identification of the initial forms carrying resistance genes is a necessary step toward successful breeding of anthracnose-resistant cultivars. Use of molecular markers will increase reliability of identification and enhance effectiveness of strawberry breeding.Materials and methods. Biological material was represented by strawberry cultivars (Fragaria × ananassa Duch.) of various ecological and geographical origin. Total genomic DNA was extracted from the fresh leaves using the CTAB methods according to Puchooa (2004). To assess the allelic state of the Rca2 anthracnose resistance gene, the SCAR marker STS-Rca2_240 was used. The SCAR marker STS-Rca2_240 was multiplexed with the microsatellite marker EMFv020 used as the positive PCR control.Results and conclusion. The SCAR marker STS-Rca2_240, mapping at about 2.8 cM from the Rca2 gene, was identified in the strawberry cultivars ‘Elianny’, ‘Troubadour’ and ‘Sudarushka’. Cvs. ‘Elianny’ and ‘Troubadour’ are presumably characterized by a dominant homozygous (Rca2Rca2) or heterozygous (Rca2rca2) genotype. Cv. ‘Sudarushka’ has the heterozygous state for the Rca2 anthracnose resistance gene (Rca2rca2). In the remaining cultivars studied, the marker STS-Rca2_240 was not detected (the prospective genotype is rca2rca2).